2010
DOI: 10.1021/nn100328a
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Schottky Barriers and Contact Band-to-Band Tunneling in Carbon Nanotube Transistors

Abstract: Devices incorporating nanoscale materials, particularly carbon nanotubes (CNTs), offer exceptional electrical performance. Absent, however, is an experimentally backed model explaining contact-metal work function, device layout, and environment effects. To fill the void, this report introduces a surface-inversion channel model based on low temperature and electrical measurements of a distinct single-walled semiconducting CNT contacted by Hf, Cr, Ti, and Pd electrodes. Anomalous barrier heights and metal-contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
0
18
1
Order By: Relevance
“…101 The two other studies that have reported measurements with different metals on CNTs with identical diameters show a decrease in Schottky barrier height with increasing work function. 67,84 However, the slope of this decrease is less than what is expected from the Schottky-Mott description (Eq. (2)) of a barrier unaffected by Fermi level pinning (dashed line in Figure 16(a)).…”
Section: A Measurements Of Schottky Barrier Heightsmentioning
confidence: 73%
See 4 more Smart Citations
“…101 The two other studies that have reported measurements with different metals on CNTs with identical diameters show a decrease in Schottky barrier height with increasing work function. 67,84 However, the slope of this decrease is less than what is expected from the Schottky-Mott description (Eq. (2)) of a barrier unaffected by Fermi level pinning (dashed line in Figure 16(a)).…”
Section: A Measurements Of Schottky Barrier Heightsmentioning
confidence: 73%
“…Ideally, a combination of activation energy, capacitive 80 and optical 87 measurement techniques should be used to study the Schottky barriers on different metals deposited on a single CNT. 84 In combination with Kelvin probe microscopy 105 to measure the work function of the different metals on the device instead of relying on tabulated values for ideal surfaces, such a study would yield a wealth of important information on the physics of Schottky barrier formation in nanoscale contacts and the influence of interface states on the Schottky barrier height.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations